Alternative to Detention Sebagai Pemenuhan Prinsip Freedom From Arbitrary detention Untuk Pengungsi Rohingya Di India (RechtJiva, 2024)
The guarantees contained in article 9(1) of the ICCPR are not being properly implemented for Rohingya refugees residing in India. The article asserts the principle of freedom from arbitrary detention, which is jus cogens. However, India has not implemented the principle as it has not fully ratified the guarantees or categories of arbitrary detention of refugees which has left a void in the application of the principle to refugees in India. This vacuum is supported by a non-existent system of handling and detention and supported by national laws that do not regulate the principle which has led to massive arbitrary arrests and violence against Rohingya refugees in Jammu and Kashmir. So in this case, the researcher raises the issue of the applicability of the Freedom from Arbitrary detention principle as Jus Cogens for the handling of Rohingya refugees in India. India, which is a state of law, adheres to dualism and monolism simultaneously, so that the principle of jus cogens can enter and force erga ormes. To fulfil this right, UNHCR established the Alternative to Detention system which has elements of necessity and proportionality to avoid arbitrary detention in the region. So that India as a state, has an obligation to fulfil this right in full based on international law and its constitution. This research uses statute approach, case approach, and conceptual approach to help researchers analyse this writing which is in the form of normative juridical.